Factors Related to Maternal Mortality in Sintang Regency 2019-2023 - Dian Ika Pratiwi; Khairulisni Saniati; Silvia Finida Hannisa; Arum Seftiani Lestari; Atri Rudtitasari; Asri Fitri Yati (Journal of Educational Innovation and Public Health, 2025)
Approximately 287,000 cases of maternal death occur during pregnancy, childbirth, and postpartum. One of the targets in the global Sustainable Development Goals (SDGs) is to reduce MMR to 70 per 100,000 live births by 2030. WHO data shows that 72.5% of maternal deaths are caused by direct factors, while the remaining 27.5% are caused by indirect factors. This study aims to determine the factors associated with maternal death in Sintang Regency in 2019-2023. The research design uses quantitative with a Cross Sectional approach. The study population is all data on maternal death cases from pregnancy, childbirth and postpartum periods from January 2019 - December 2023 obtained from the Sintang Regency Health Office. The sampling technique uses total sampling . The results of the study obtained variables of bleeding (p value 0.017), infection (p value 0.847), eclampsia (p value 0.026), age (p value 0.018) and parity (p value 0.900). There is a relationship between bleeding, eclampsia and age with maternal mortality in Sintang Regency in 2019-2023. There is no relationship between infection and parity with maternal mortality in Sintang Regency in 2019-2023. It is hoped that the relevant health services will improve health service efforts to reduce MMR.